Intra-amygdala microinjection of TNF-α impairs the auditory fear conditioning of rats via glutamate toxicity. (February 2015) - Jing, He; Hao, Yongxin; Bi, Qiang; Zhang, Jiaozhen; Yang, Pingting
Highlights: Intra-amygdala infusion of TNF-α impaired the behaviors of auditory fear conditioning. TNF-α induced neurotoxicity via excessive glutamate release. NMDA receptor antagonist can reserve the impairments induced by TNF-α. Abstract: During an inflammatory or infectious process, innate immune cells produce large amount of pro-inflammatory cytokines that act on the brain to cause cognitive dysfunctions. Tumor necrosis factor alpha (TNF-α) is one of the main pro-inflammatory cytokines. Thus, it is important to study how the excessive TNF-α affects the cognitive functions of central nervous system and possible antagonists to its effects. In the present study, we conducted behavioral experiments of rats to determine whether murine TNF-α administered directly into the brain would elicit behavioral effects related to learning and memory impairments. Rats subjected to single-dose intra-amygdala TNF-α infusion showed a significant delay in the acquisition and extinction of auditory fear conditioning. Accordingly, the glutamate level of the tissue samples from amygdala was elevated after the TNF-α treatment. Furthermore, pharmacological blockade of NMDAR before the TNF-α treatment reversed the TNF-α induced impairments in fear learning. Our findings suggest that TNF-α can impair the learning and memory functions through glutamate–NMDAR neurotoxicity, and present the possibility to develop therapeutic modalities directing at glutamate transmission for the treatment of neuro-inflammative dysfunctions.